Analysis of the Relationship between Research Groups and Firms - Antunes, Luiz Guilherme Rodrigues; Souza, Thais Assis de; Antonialli, Luiz Marcelo (Revista de Negócios, 2021)
This research focuses on the interaction between universities and firms, considering a society based on the knowledge economy. The aim is to identify relationships between research groups and firms that most contribute to the innovative performance of Brazilian Public Educational Institutes (PEIs). The adopted database was the tabular plan of 2010, from the Research Groups Directory of CNPq. The method was based on statistical techniques, such as Spearman Correlation, Cluster Analysis, ANOVA and Discriminant Analysis. As a result, the most relevant relationships obtained were the transfer of technology developed by the group to the partner; non-routine engineering activity, including development/manufacturing of equipment for the group; and scientific research with considerations of immediate use, respectively. It is therefore emphasized that the encouragement of certain relationships can support an increase in the innovative potential of PEIs. As practical contributions, it is argued that these results help PEIs on determining innovative paths, which are based on development and transfer of technology, as well as the realization of practice-oriented research.